Effects of different weed control periods on the productivity of corn crop - Ramos, Levi Ribas de Miranda; Pitelli, Robinson A. (Pesquisa Agropecuaria Brasileira, 1994)
Two field trials were carried out aiming to study the effects of different weed control periods on the productivity of the corn crop (Zea mays L.). Both experiments were installed in the randomized block design with four replications. The treatments were divided in two groups. In the first group the weeds grew together with the corn crop, since the sowing date until 00, 14, 28, 42, 56, 70, 84 and 98 days of the crop cycle. In both essays, the predominant weeds were Indigofera hirsuta L. and Cenehrus echinatus L. In the essay sowed in December, the weeds emergence and growth were very quick and fast, achieving great influence on the crop growth and on productivity. The values of the total period of weed interference (PTPI) and the pre-interference period (PAI) were 42 days and less than 14 days, respectively.